Analysis of the Test Methods for High Modulus Fibers and Composites 1973
DOI: 10.1520/stp36487s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Free Edge upon the Strength of Angle-Ply Laminates

Abstract: Strength characterization of the fiber-reinforced laminated composite materials is quite often accomplished through the utilization of the finite-width tension coupon specimen. Recent analytical studies have shown that the state of stress in the vicinity of the free edge of such a laminate is fully three dimensional in nature and may not be predicted by laminated plate theory. Furthermore, experimental results have revealed that while the strength of angle-ply tensile coupons of certain fiber orientations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…These are predicted to be the locations of greatest susceptibility to delamination when AWJ cutting. The interlaminar stresses are highly sensitive to the stacking sequence [193][194][195] and are largest near free edges [196,197] and decrease rapidly with distance from free boundaries [128]. This is consistent with the numerical results of Fig.…”
Section: Delamination Onset When Awj Cuttingsupporting
confidence: 83%
“…These are predicted to be the locations of greatest susceptibility to delamination when AWJ cutting. The interlaminar stresses are highly sensitive to the stacking sequence [193][194][195] and are largest near free edges [196,197] and decrease rapidly with distance from free boundaries [128]. This is consistent with the numerical results of Fig.…”
Section: Delamination Onset When Awj Cuttingsupporting
confidence: 83%
“…Since it is felt that the experimental observation of free-edge effects and the conduction of corresponding failure analyses is a very special field and worth a separate review work, we will only cite some references on this topic, yet we will not go into more details. The interested reader may refer to some experimental studies reported in for example [4][5][6]10,12,37,58,68,72,81,87,88,120,[124][125][126] and may consult further references cited therein.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Experimental investigations are reported in e.g. [68][69][70][71][72][73]. The interested reader may refer to various available detailed surveys on this topic, see e.g.…”
Section: Introductionmentioning
confidence: 99%